Residence parcel drop box with multi-layer authentication using cyber physical system - Tan, Kah Hsing (2023)
This project is development-based for academic purposes. It will provide the Final Year Project students with the methodology planning, concept thinking and design of a residential parcel drop box with multi-layer authentication using Cyber Physical System. The project will be illustrated through the development of a parcel drop box system. The parcel drop box system will be primarily use for residences to solve the issue of failed delivery attempts by courier delivery personnel because of no recipient absent at the delivery address. The courier delivery personnel will be able to deliver parcels conveniently by dropping off the parcel into the drop box system without the recipient to be present to receive the parcel. The parcel drop box can authenticate the parcel, unlock the drop box door, and receive the parcel from the courier delivery personnel. A mobile application is also developed using Flutter to unlock the door of the parcel drop box and to input the tracking number of the incoming parcel. A Raspberry Pi computer is well suited for a project that utilizes digital circuits and software. Therefore, a Raspberry Pi 3 Model B will be utilized in the development of this project. This project aims to reduce failed deliveries of e-commerce parcels to recipient addresses during the non-present period and reduce parcel theft and damages due to parcel throwing into the delivery address compound.